2018
DOI: 10.1200/jgo.18.56200
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation Toward Cancer Incidence: An Epidemiological Systematic Review

Abstract: Background: It is well accepted that environment- and lifestyle-related factors (e.g., tobacco, diet, obesity and environmental pollutants) play a critical role in the development of nearly all cancers. Inflammation seems to be a major process that all of these risks factors have in common. Insight in the role of inflammation toward cancer development might have implications in prevention, early diagnosis and treatment of cancer (e.g., by selectively suppressing certain proinflammatory mediators). Aim: The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…7 Epidemiological studies have demonstrated the association between solid tumors and inflammation. 9 A quarter of all cancers are estimated to be attributable to chronic inflammation. 10 Chronic inflammation can arise from intrinsic host factors as with the case of inflammatory bowel disease.…”
Section: Inflammation and Cancermentioning
confidence: 99%
“…7 Epidemiological studies have demonstrated the association between solid tumors and inflammation. 9 A quarter of all cancers are estimated to be attributable to chronic inflammation. 10 Chronic inflammation can arise from intrinsic host factors as with the case of inflammatory bowel disease.…”
Section: Inflammation and Cancermentioning
confidence: 99%
“…For many years, it has been evident that the frequency of cancerous tumors correlates with the frequency of injury/inflammation events (Coussens and Werb, 2002; Il’yasova et al, 2005; Todoric et al, 2016; Michels et al, 2018). In both regeneration and cancer, the blocks to adult cell growth are removed; but in normal regeneration, the blocks are restored (Hart, 2002; Landén et al, 2016).…”
Section: Introductionmentioning
confidence: 99%